Medicinal potentials of Strobilanthes crispus (l.) and Orthosiphon stamineus benth. in the management of kidney stones: a review and bibliometric analysis - Zakaria, Nor Hafizah; Abdul Majid, Fadzilah Adibah; Mohd Helmi, Nur Ain Nadhirah; Awang, Anis Fadhlina Izyani; Sheikh Mohamed, Hassan Ibrahim (Elsevier, 2023)
Introduction In Malaysia, the consumption of tea made from the leaves of Strobilanthes crispus, Orthosiphon stamineus, and their combination is believed by the local people to alleviate kidney stone disease. Therefore, this review was conducted to validate the traditional claims based on the scientific evidences of kidney stones remedies using S crispus and O stamineus. The scientific progress that has evolved over a period of time will be examined using bibliometric analysis.